2006
DOI: 10.1134/s1063780x06080058
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the chaotic dynamics of an electron beam with a virtual cathode in an external magnetic field

Abstract: -The effect of the strength of the focusing magnetic field on chaotic dynamic processes occurring in an electron beam with a virtual cathode, as well as on the processes whereby the structures form in the beam and interact with each other, is studied by means of two-dimensional numerical simulations based on solving a self-consistent set of Vlasov-Maxwell equations. It is shown that, as the focusing magnetic field is decreased, the dynamics of an electron beam with a virtual cathode becomes more complicated du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…It has been also demonstrated that for the strong magnetic fields the output power is saturated on the low power level. The same results have been also obtained in theoretical and experimental works [22][23][24]. However, the physical mechanisms of such power behavior are still uninvestigated in the most cases.…”
supporting
confidence: 74%
See 4 more Smart Citations
“…It has been also demonstrated that for the strong magnetic fields the output power is saturated on the low power level. The same results have been also obtained in theoretical and experimental works [22][23][24]. However, the physical mechanisms of such power behavior are still uninvestigated in the most cases.…”
supporting
confidence: 74%
“…8 and based on 2.5D model developed in our previous work. 24 The equations of charged particles motion (2) are used for the electron beam simulation and solved numerically by means of B oris algorithm. 27 The electromagnetic fields in the drift chamber of REB are obtained by means of the numerical solution of Maxwell's equations (1) in cylindrical geometry on the shifted spatiotemporal meshes.…”
mentioning
confidence: 99%
See 3 more Smart Citations